Role of Somatic Antigen of Vibrio Cholerae in Adhesion to Intestinal Mucosa - Chitnis, D. S.; Sharma, K. D.; Kamat, R. S. (Journal of Medical Microbiology, 1982)
SUMMARY The in-vitro adhesion of Vibrio cholerae to intestinal mucous membrane was studied in isolated adult-rabbit ileal loops. Antisomatic antiserum against V. cholerae Inaba could inhibit adhesion of three different strains of V. cholerae Inaba but had no effect on the adhesion of two different strains of enterotoxigenic NAG vibrios. The antiserum’s bacterial agglutinin titre was 320, its anti-Inaba lipopolysac-charide (LPS) titre was 16 000 and its anti-flagellar antibody titre was 3200. Conversely, anti-live V. cholerae Inaba antiserum absorbed with boiled cells of Inaba and devoid of antisomatic antibody, could not inhibit adhesion of the same three strains of V. cholerae Inaba. This antiserum had no anti-LPS or bacterial agglutinin activity, but its anti-flagellar antibody titre was 32 000. Thus, ability to inhibit adhesion of V. cholerae could be correlated only with antisomatic (anti-LPS) antibody activity. Antisomatic antiserum had no activity against ‘adhesin’, a V. cholerae surface antigen described by Freter. Conversely anti-live V. cholerae antiserum absorbed with boiled cells showed anti-adhesin activity even at a dilution of 1 in 200. LPS preparations from V. cholerae strain 569B Inaba could inhibit adhesion of two different Inaba strains to the intestinal mucous membrane. It is concluded that the somatic antigen plays a major role in the adhesion of V. cholerae to the intestinal mucous membrane.